2013
DOI: 10.1038/mi.2012.109
|View full text |Cite
|
Sign up to set email alerts
|

The C-C motif chemokine ligands CCL5, CCL11, and CCL24 induce the migration of circulating fibrocytes from patients with severe asthma

Abstract: The C-C motif chemokine ligand 5 (CCL5), CCL11, and CCL24 are involved in the pathogenesis of asthma, and their function is mainly associated with the airway recruitment of eosinophils. This study tested their ability to induce the migration of circulating fibrocytes, which may contribute to the development of irreversible airflow obstruction in severe asthma. The sputum fluid phase (SFP) from patients with severe/treatment-refractory asthma (PwSA) contained elevated concentrations of CCL5, CCL11, and CCL24 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
80
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(82 citation statements)
references
References 40 publications
2
80
0
Order By: Relevance
“…Fcs may instead play a major role in the recall phase of the allergic response, given that in allergic asthmatics every allergen exposure is associated with a progressive increase in the density of these cells in the bronchial mucosa from 4 to 24 h post allergen inhalation (Schmidt et al, 2003). In support of the ability of Fcs to amplify TH2L-driven inflammatory responses in the airways, a recent study from my laboratories has demonstrated that circulating Fcs and mDCs from allergic asthmatics similarly induce the proliferation of autologous circulating memory CD4 + THLs and the predominant release of the TH2 cytokines IL-4 and IL-5 from effector CD4 + THLs when pulsed with the clinically relevant allergen (Isgrò et al, 2013b).…”
Section: Amplification Of Inflammation Induced By Allergen Exposure Amentioning
confidence: 99%
See 4 more Smart Citations
“…Fcs may instead play a major role in the recall phase of the allergic response, given that in allergic asthmatics every allergen exposure is associated with a progressive increase in the density of these cells in the bronchial mucosa from 4 to 24 h post allergen inhalation (Schmidt et al, 2003). In support of the ability of Fcs to amplify TH2L-driven inflammatory responses in the airways, a recent study from my laboratories has demonstrated that circulating Fcs and mDCs from allergic asthmatics similarly induce the proliferation of autologous circulating memory CD4 + THLs and the predominant release of the TH2 cytokines IL-4 and IL-5 from effector CD4 + THLs when pulsed with the clinically relevant allergen (Isgrò et al, 2013b).…”
Section: Amplification Of Inflammation Induced By Allergen Exposure Amentioning
confidence: 99%
“…They participate in extracellular matrix (EM) remodeling through the production of some of the collagens and noncollagenous EM components synthesized in larger quantities by fibroblasts (Bucala et al, 1994;Chesney et al, 1998;Abe et al, 2001;Bianchetti et al, 2012b), and are also involved in collagen uptake and degradation (Bianchetti et al, 2012b). These cells can exhibit predominant proinflammatory activities or predominant profibrotic properties at tissue sites, depending on the host's response to diverse environmental insults (allergens, viruses, irritants) (Isgrò et al, 2013b) and on the characteristics of the local cell infiltrate and cytokine milieu (Bellini et al, 2012;Sazuka et al, 2014). Similarly to other cells with combined antigenpresenting function and mesenchymal cell-like features (Muñoz-Fernández et al, 2006;Saada et al, 2006), they acquire a myofibroblast-like phenotype in vitro and at the tissue sites because of the expression of adhesion molecules also present on the surface of these cells (Bianchetti et al, 2012b) and the inducible synthesis of the intracellular contractile protein α-smooth muscle actin (α-SMA) (Abe et al, 2001;Schmidt et al, 2003;Mori et al, 2005;Saunders et al, 2009).…”
Section: Background Information On Fc Identification and Isolationmentioning
confidence: 99%
See 3 more Smart Citations